2020
DOI: 10.1101/2020.08.14.20175018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socio-demographic, clinical, hospital admission and oxygen requirement characteristics of COVID-19 patients of Bangladesh

Abstract: Background: Clinical presentation hospital admission and outcome of COVID-19 pandemic are different from one country to another. So every country should have their own data regarding COVID-19. Subjects and Methods: This was an online cross-sectional survey carried out in RT-PCR positive COVID-19 adult patient. A preformed questionnaire adapted in Google form and circulated through online to collect data. Informed consent was ensured before participation in this study. Results: We have studied of 305 RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…We also found that patient’s mean age was 35.33 ± 14.90, whereas two other studies from our country reported that the mean age was 36.32 ± 12.36 and 42.59 ± 14.43, respectively [ 23 , 28 ]. Our study participants ranged in age from 20 to 60 years old.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…We also found that patient’s mean age was 35.33 ± 14.90, whereas two other studies from our country reported that the mean age was 36.32 ± 12.36 and 42.59 ± 14.43, respectively [ 23 , 28 ]. Our study participants ranged in age from 20 to 60 years old.…”
Section: Discussionsupporting
confidence: 41%
“…Previously, one study from Iran showed that diabetes (16.3%) and cardiovascular disorder (21%) were the most frequent comorbidities among the COVID-19 sufferer. At the same time, research from our country reported that hypertension (19.2%) and bronchial asthma (17.6%) were the two most common co-morbidities [ 28 ]. Cardiovascular complication, which includes myocarditis, acute cardiac injury, myocardial injury, arrhythmia, stroke, heart failure, cardiac shock, multisystem inflammatory syndrome, arterial and venous thrombotic events, and coagulopathy, is another common comorbidity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the clinical outcomes of COVID-19 and its association with various pathophysiological factors, no comprehensive study has been conducted in Bangladesh. Some of the studies did not include a large sample size [ [6] , [7] , [8] ], so understanding the aforementioned relationship of COVID-19 symptoms with comorbidities and biochemical parameters from previous studies was not possible. In particular, the long-term complications or short-term outcomes among patients who have recovered from COVID-19 have not been studied with the necessary rigor.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the clinical outcomes of COVID-19 and its association with various pathophysiological factors, no comprehensive study has been conducted in Bangladesh. As some of the studies were not conducted for a large sample size, 6-8 understanding a bigger picture of the aforementioned relationship of COVID-19 symptoms with comorbidities and biochemical parameters from previous studies was not possible. Especially, the long-term complications among patients recovered from COVID-19 have not been conducted with necessary rigor and comprehension.…”
Section: Introductionmentioning
confidence: 99%